Pedra e cal: os construtores de Vila Rica noo século XVIII (1730-1800) - Fabiano Gomes da Silva (2007)
This reserarch aims to analyze a social experience of one part of the mining constructors as the masons, stonemasons and carpenters, who had lived and acted in Vila Rica from 1730 to 1800 a period that was marked for interventions and transformations in this colonial urban nucleous. We also bring out the participation of the slaves and freedmen working with the constructors teams. showing their importance, not only in the labour market but also in their daily work. The study of the colonial population who had dedicated themseilves for the mechanical work, showed their importance for the understanding of the social composition and cultural mobility in the village.